A meta-analysis of the effects of long-term oxygen therapy combined with exercise rehabilitation on exercise capacity, cardiopulmonary function, and quality of life in patients with COPD - Muge, Qi; Suriguga; Yuqing; Aronggaowa; Taojin; Chen, Lanying (Frontiers in Medicine, 2025)
ObjectiveTo assess the effectiveness of long-term oxygen therapy (LTOT) combined with exercise rehabilitation vs. exercise rehabilitation alone in improving exercise capacity, cardiopulmonary function, and quality of life in chronic obstructive pulmonary disease (COPD) patients.MethodsA comprehensive literature search was conducted in the Chinese Biomedical Literature Database (CBM), Wanfang, China National Knowledge Infrastructure (CNKI), Cochrane Library, EMBASE, ScienceDirect, and PubMed for studies published from January 2010 to the present. Controlled clinical trials comparing oxygen therapy and/or exercise rehabilitation in COPD patients were included. Two independent reviewers extracted data and assessed risk of bias using the Cochrane Handbook (version 5.3). Meta-analysis was performed using RevMan 5.3.ResultsNine studies (N = 703) met inclusion criteria. Compared with the control group (CG), the combined LTOT and exercise group showed significant improvements in 6-min walk distance (6MWD), forced expiratory volume in 1 s (FEV1), and FEV1/FVC ratio (P < 0.05). PaO2 levels tended to be higher but showed substantial heterogeneity. No significant differences were observed in blood oxygen saturation, heart rate, or PaCO2. Quality of life significantly improved in the combined therapy group.ConclusionLTOT combined with exercise rehabilitation is more effective than exercise alone in improving exercise capacity, pulmonary function, and quality of life in COPD patients. However, cardiac benefits remain unclear, warranting further studies.